What is the Diagnosis? - Baggio Junior, Jose Mario; Mosquera, Joubert Ariel Pereira; Gomes, Luis Gustavo Ferreira; Gali, Wagner Luis; Sarabanda, Alvaro Valentim Lima (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Patient T.D., 23 years old, female, with corrected transposition of the great arteries, complete atrioventricular block with narrow QRS, submitted to bicameral pacemaker implantation at 13 years of age, with generator replacement three years ago. She has a good functional capacity, but complains of fatigue in the face of intense effort.